ANALISIS DAMPAK COVID-19 PADA VOLUME TRANSAKSI SAHAM DAN HARGA SAHAM (STUDI KASUS PADA INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2020) - Yarahim, Bunai; Ramadhani Ridarto, Visinamitri; M. Fasda Andriatama, M. Fasda Andriatama (Research in Accounting Journal (RAJ), 2021)
Shares are one of the capital market instruments that can be defined as a sign of one's or one-sided capital participation (business entity) in a company or limited liability company. The current factor is the impact of the Covid-19 virus on stock transaction volume and stock prices. So it is very necessary to analyze the impact of Covid-19 on the volume of stock transactions and stock prices with the object of research being the mining industry. This research uses secondary data and this data analysis method uses qualitative descriptive analysis techniques. The results of this research show that the volume of stock transactions and share prices affected by COVID-19 have decreased and increased at a certain time, with the encouragement of China's policy which began to loosen import restrictions.